2019
DOI: 10.1111/anae.14682
|View full text |Cite
|
Sign up to set email alerts
|

Screening for delirium after surgery: validation of the 4 A's test (4AT) in the post‐anaesthesia care unit

Abstract: Summary Postoperative delirium is common and has multiple adverse consequences. Guidelines recommend routine screening for postoperative delirium beginning in the post‐anaesthesia care unit. The 4 A's test (4AT) is a widely used assessment tool for delirium but there are no studies evaluating its use in the post‐anaesthesia care unit. We evaluated the performance of the 4AT in the post‐anaesthesia care unit in a tertiary German medical centre. Adults who were able to provide informed consent, were not schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 26 publications
0
62
1
2
Order By: Relevance
“…Among them, we excluded 57 studies, 2 of which were validation studies of the 4AT using the same dataset with already included studies [ 23 , 24 ]. As a result, a total of 13 articles that met the inclusion criteria were finally identified in our systematic review [ 10 , 11 , 12 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, we excluded 57 studies, 2 of which were validation studies of the 4AT using the same dataset with already included studies [ 23 , 24 ]. As a result, a total of 13 articles that met the inclusion criteria were finally identified in our systematic review [ 10 , 11 , 12 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, four studies reported various cut-off scores for the DTA of the Nu-DESC (Hargrave et al, 2017;Leung et al, 2008;Neufeld et al, 2013;Saller et al, 2019; Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It contains the four‐item Abbreviated Mental Test (AMT4: age, date of birth, current year and place), evidence of acute change or fluctuation, alertness and the month backwards test for assessing attention. In a recent study, we evaluated an adult cohort of 543 patients aged between 18 and 96 years and found excellent performance of the 4AT to diagnose delirium in the recovery area in a tertiary German medical centre . In order to examine the properties of the 4AT to diagnose delirium in older patients in this setting, we subsequently analysed a subset of 143 patients from the original study that were 65 years or older.…”
mentioning
confidence: 99%